Development of safety self-audit mechanism for chemical laboratories in higher learning institute: A case study in Universiti Malaya / Ahmad Fahim Mahmud - Ahmad Fahim, Mahmud (2022)
Safety compliance and implementation of best practices are commonly enhanced through scheduled auditing and subsequent improvement processes. The audits are commonly conducted by third parties (internal or external). However, when the number of laboratories involved are in hundreds, third party audits may not take place as per schedule and may affect the safety level of the laboratories. One of the means to overcome this issue is by developing a self-audit mechanism that can be used by the person(s) in charge of the laboratories itself to conduct the audit. Therefore, in this work, a comprehensive self-audit checklist was developed by taking into consideration safety related activities and facilities in typical chemical laboratories. Subsequently, the checklist was used to gather information on selected laboratories. The self-audit checklist consisted of nineteen (19) key categories. Guideline to use the checklist is also provided in the self-audit mechanism. The practicality of the checklist developed was validated by auditing one, two and three chemical laboratories in Faculty of Engineering, Faculty of Medicine, and Faculty of Science, respectively. The result showed that the safety self-audit mechanism is practical as a tool to conduct a comprehensive safety audit in chemical laboratories, with minimum time and monetary requirement. Hence, the study has proven that the safety self-audit mechanism developed can be used to initiate safety self-audit practices in chemical laboratories in higher learning institution in Malaysia.